See you at San Diego an oral history of Comic-Con, fandom, and the triumph of geek culture - Klickstein, Mathew 1981- (Fantagraphics Books, 2022)
"A comprehensive chronicle of Comic-Con International and modern geekdom itself as told through countless intimate, hilarious, and often-thought provoking stories by nearly fifty of the most integral members of today's convention and fandom community."--
Keywords: San Diego Comic-Con; Comic; Comic book fans; Comic books, strips, etc / Marketing; Motion pictures and comic books; Popular culture / United States; Science fiction conventions / California / San Diego; Science fiction conventions; Popular culture; California / San Diego / https://id.oclc.org/worldcat/entity/E39PBJcgBTyH8pqbcDw7Q4kv73; United States / https://id.oclc.org/worldcat/entity/E39PBJtxgQXMWqmjMjjwXRHgrq; Fandom convention; Fandom subculture; Literary fandom; interviews; Interviews